Hypertension in the Pediatric Kidney Transplant Recipient - Charnaya, Olga; Moudgil, Asha (Frontiers in Pediatrics, 2017)
Hypertension after kidney transplant is a frequent occurrence in pediatric patients. It is a risk factor for graft loss and contributes to the significant burden of cardiovascular disease in this population. The etiology of post-transplant hypertension is multifactorial including donor factors, recipient factors, medications and lifestyle factors similar to those prevalent in the general population. Ambulatory blood pressure monitoring has emerged as the most reliable method for measuring hypertension in pediatric transplant recipients and many consider it to be essential in the care of these patients. Recent technological advances including measurement of carotid intima media thickness, pulse wave velocity and myocardial strain using specked echocardiography and cardiac magnetic resonance imaging has improved our ability to assess cardiovascular disease burden. Since hypertension remains under recognized and inadequately treated, an early diagnosis and an appropriate control should be the focus of therapy to help improve patient and graft survival.